Disadvantageous Decision-Making as a Predictor of Drop-Out among Cocaine-Dependent Individuals in Long-Term Residential Treatment - Stevens, Laura; Betanzos-Espinosa, Patricia; Crunelle, Cleo L.; Vergara-Moragues, Esperanza; Roeyers, Herbert; Lozano, Oscar; Dom, Geert; Gonzalez-Saiz, Fransisco; Vanderplasschen, Wouter; Verdejo-García, Antonio; Pérez-García, Miguel (Frontiers in Psychiatry, 2013)
Background: The treatment of cocaine-dependent individuals (CDI) is substantially challenged by high drop-out rates, raising questions regarding contributing factors. Recently, a number of studies have highlighted the potential of greater focus on the clinical significance of neurocognitive impairments in treatment-seeking cocaine users. In the present study, we hypothesized that disadvantageous decision-making would be one such factor placing CDI at greater risk for treatment drop-out. Methods: In order to explore this hypothesis, the present study contrasted baseline performance (at treatment onset) on two validated tasks of decision-making, the Iowa Gambling Task (IGT) and the Cambridge Gamble Task (CGT) in CDI who completed treatment in a residential Therapeutic Community (TC) (N=66) and those who dropped out of TC prematurely (N=84). Results: Compared to treatment completers, CDI who dropped out of TC prematurely did not establish a consistent and advantageous response pattern as the IGT progressed and exhibited a poorer ability to choose the most likely outcome on the CGT. There were no group differences in betting behavior. Conclusions: Our findings suggest that neurocognitive rehabilitation of disadvantageous decision-making may have clinical benefits in CDI admitted to long-term residential treatment programs.